2020
DOI: 10.1111/rode.12708
|View full text |Cite
|
Sign up to set email alerts
|

Can individuals’ beliefs help us understand nonadherence to malaria test results? Evidence from rural Kenya

Abstract: In malaria‐endemic countries about a quarter of test‐negative individuals take antimalarials (artemisinin‐based combination therapies [ACTs]). ACT overuse depletes scarce resources for subsidies and contributes to parasite resistance. As part of an experiment in Kenya that provided subsidies for rapid diagnostic test and/or for ACTs conditionally on being positive, we studied the association between beliefs on malaria status (prior and posterior the intervention) and decisions to get tested and to purchase ACT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
2
0
0
Order By: Relevance
“…In particular, we found that those who had higher confidence in RDT testing were more likely to adhere to a negative test result. We did not find that confidence in testing affected whether an individual got tested, similar to a previous study [ 38 ]. However, as in that study, the bar to testing was very low for participants: the RDT was free, a member of the study team would come and test at the household, and participants could get a free ACT if they tested positive for malaria.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In particular, we found that those who had higher confidence in RDT testing were more likely to adhere to a negative test result. We did not find that confidence in testing affected whether an individual got tested, similar to a previous study [ 38 ]. However, as in that study, the bar to testing was very low for participants: the RDT was free, a member of the study team would come and test at the household, and participants could get a free ACT if they tested positive for malaria.…”
Section: Discussionsupporting
confidence: 91%
“…These results suggest that people learn from their experience with testing and treatment. Our results are consistent with findings from population-level studies that show that greater access to testing increases people’s confidence in malaria testing [ 38 ] and can reduce inappropriate use of ACTs [ 22 , 39 ]. Unlike a previous study [ 40 ] however, we did not find any statistically significant effects of testing experience on confidence in AL, perhaps because confidence in AL was higher compared to confidence in RDTs, and adherence to a positive RDT was close to 100%, thus limiting the scope for learning about AL effectiveness.…”
Section: Discussionsupporting
confidence: 90%